The Effectiveness of the Use of Audio Visual as a Learning Media for Speaking Skills and Reading Skills of Tsanawiyah Students - Nuraini, Rini; Rambe, Mirza Syadat; Irwanto, Irwanto; Moha, Luqman; Fiidznillah, Rizki (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
In this increasingly sophisticated era, students are required to be able to have speaking and reading skills. However, due to the lack of effectiveness of teachers in using learning media, many students feel that learning feels monotonous so that students do not want to develop and practice their speaking and reading skills. The purpose of this study is to determine the effectiveness of the use of audio visuals as a learning medium for speaking skills and reading skills of tsanawiah students. This research method uses a quantitative research method, where the data is obtained from the results of online questionnaire distribution. The results of the study show that audio-visual media is effective on students' speaking and reading skills. From the study, it can be concluded that the use of audio visuals as a learning medium has proven to be effective. The limitation of this study is that researchers can only conduct research on audio-visual learning media even though there are still many other learning media that can be used as alternatives in improving students' speaking and reading skills. The researcher hopes that the next researcher will be able to conduct research related to students' speaking and reading skills but by using other learning media. This study also recommends to future researchers to use this research as a reference in conducting research on improving students' speaking and reading skills through audio visuals.